2011
DOI: 10.1128/aac.00772-10
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin Protects against Anthrax Lethal Toxin-Induced Activation of the Nlrp1b Inflammasome

Abstract: Anthrax lethal toxin (LT) is the major virulence factor for Bacillus anthracis. The lethal factor (LF) component of this bipartite toxin is a protease which, when transported into the cellular cytoplasm, cleaves mitogen-activated protein kinase kinase (MEK) family proteins and induces rapid toxicity in mouse macrophages through activation of the Nlrp1b inflammasome. A high-throughput screen was performed to identify synergistic LT-inhibitory drug combinations from within a library of approved drugs and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…We and others have investigated the utility of screening with approved drugs to identify potential therapeutics that can be used against EBOV and other biological threat agents or emerging diseases (43,(48)(49)(50). Often with such diseases, conventional drug development is challenging because of both cost and ability to perform controlled clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have investigated the utility of screening with approved drugs to identify potential therapeutics that can be used against EBOV and other biological threat agents or emerging diseases (43,(48)(49)(50). Often with such diseases, conventional drug development is challenging because of both cost and ability to perform controlled clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Each compound was initially tested at one concentration targeted between the IC 50 and IC 90 concentrations obtained from the eight-point dose-response confirmation with eGFP-EBOV. Results of these VLP entry assays indicate that 25 of the 30 active compounds tested inhibited EBOV-VLP entry by >90% ( Table 2).…”
Section: Prioritized Active Compounds Inhibit Ebov Viral Entry In Vitromentioning
confidence: 99%
“…This novel strategy targets an allosteric site at the dimer interface of caspases by using small molecules that have better drug-like properties (MacKenzie et al, 2010). More recently the organogold compound auranofin was shown to prevent anthrax LT-mediated activation of the Nlrp1 and Nlrp3 inflammasomes, probably by direct inhibition of caspase-1 (Newman et al, 2011). Two protease inhibitors, ritonavir and disulfiram, were shown to inhibit caspase-1 activation and suggested to be useful in abrogating IL-18 release (Nobel et al, 1997;Sloand et al, 2000;Kast, 2008).…”
Section: Inflammasome Blockers As Novel Therapeuticsmentioning
confidence: 99%
“…), which brings us back to P2X7R pharmacology. Alternatively, scattered evidence suggests that drugs inhibiting voltage-gated K + channels, i.e., idebenone, may also prevent inflammasome activation (Newman et al, 2011).…”
Section: Inflammasome Blockers As Novel Therapeuticsmentioning
confidence: 99%
“…Therefore, inhibiting K + efflux or increasing K + concentrations in the extracellular environment may provide a strategy to inhibit NLRP1 and NLRP3 receptor activation. An experimental study provided evidence that inhibiting voltage-gated K + channels (using Idebenone) prevented NLRP1 receptor activation following anthrax lethal toxin treatment in mouse macrophages (Newman et al, 2011). In addition, an experimental study showed that glibenclamide, an orally active sulfonylurea receptor 1 (SUR1) inhibitor towards the regulatory subunit of ATP-sensitive K + channels (K + ATP ) used to treat Type 2 diabetes have shown a remarkable ability to inhibit caspase-1 activation, and processing and secretion of IL-1β from murine and human macrophages through an unknown mechanism independent of SUR1 inhibition (Lamkanfi et al, 2009).…”
Section: Targeting Signalling Pathways -Nf-κb and Mapk(s) Pathwaymentioning
confidence: 99%